Kebijakan Keamanan Teknologi Informasi Pada Perangkat Keras Di Perusahaan Distributor Sepatu - Andry, Johanes Fernandes; Wijaya, Andreas; Bernanda, Devi Yurisca; Geasela, Yemima Monica; Yusup, Cristiano Ronaldo; Chandra, Johansen Christian; Alexandre, Jonathan (Universitas Bunda Mulia, 2023)
A shoe distributor company is a company engaged in the distribution of shoes to consumers. In its daily practice, shoe distributor companies have not implemented the IT Security Policy properly. Then the Community Service program is carried out with the aim of enforcing the established information security policy. The method is in the form of exposing material to shoe distributor companies regarding the importance of having and implementing an IT Security Policy, especially an IT Security Policy on Hardware. The implementation of the program was carried out in two major stages, namely the pre-implementation stage where the research team received data on company problems, conducted an analysis of these problems, prepared presentation materials/materials and the implementation stage where the PKM implementing team coordinated and executed the PKM material presentation activities. The presentation of the material was carried out face to face at the Head Office of the shoe distributor company. The activity began with an opening & introductory session, followed by presentation of material, which was divided into five major topics, namely explanation of system security, explanation of Policy, Standards, Procedures, Guidelines, explanation of Sample Template Policy, Standards, Procedures, Guidelines, explanation of Hardware security, and explanation of company Case Study. Then, the activity continued in the question-and-answer session and after that continued with the evaluation activities carried out by filling out the Google feedback link in the program implementation form for the participants. The results obtained in the PKM activities were that the implementation was carried out well and was beneficial for the shoe distributor company with several suggestions for improvement, namely the delivery of material that could be slower, examples that were more specific and appropriate.